Fatty liver hemorrhagic syndrome in a hen - Figueroa, Alejandra; Acevedo, Hernando D.; Schild, Carlos; Olivares, Roberto W. I.; Asin, Javier; Henderson, Eileen; Uzal, Francisco A. (Brazilian Journal of Veterinary Pathology, 2025)
Diffusely pale yellow, soft, friable liver with focal rupture of the right lobe and regionally extensive intrahepatic andcoelomic hemorrhage